2023
DOI: 10.3390/antiox12030655
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzyme Activity and Serum HSP70 Concentrations in Relation to Insulin Resistance and Lipid Profile in Lean and Overweight Young Men

Abstract: Oxidants are generated by all cells during normal oxidative respiration, and as long as they are under the control of appropriate mechanisms, they act as intracellular signaling molecules participating in complex functions. Oxidative stress can also affect insulin levels in the body. The production of reactive oxygen species by-products can lead to insulin resistance. Heat shock proteins (70 kDa) protect cells from the damaging effects of heat shock but also oxidative stress. The aim of the study was to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…However, the relationship between CAT and T2D risk on the age subgroup analyses contradicted the previous findings, which revealed that older people have a higher T2D risk than the younger ones [31,35]. The proposed reason for the conflicting results on CAT activity could be a cellular response as a compensatory adaptation to OS during the downregulation of CAT, genetic mechanisms and body fat accretion among individuals, and a disturbance in the protein tyrosine kinase and protein tyrosine phosphatase in cell signaling pathways during aging on impaired CAT activity [48].…”
Section: Discussionmentioning
confidence: 69%
“…However, the relationship between CAT and T2D risk on the age subgroup analyses contradicted the previous findings, which revealed that older people have a higher T2D risk than the younger ones [31,35]. The proposed reason for the conflicting results on CAT activity could be a cellular response as a compensatory adaptation to OS during the downregulation of CAT, genetic mechanisms and body fat accretion among individuals, and a disturbance in the protein tyrosine kinase and protein tyrosine phosphatase in cell signaling pathways during aging on impaired CAT activity [48].…”
Section: Discussionmentioning
confidence: 69%
“…The reduction of exercise-induced inflammation and oxidative stress is also exerted in the recovery process of injured tissues after exercise through the chaperone function of HSP70. There was a change in serum HSP70 concentration immediately after 60 minutes of exercise [90]. Serum-sensitive HSP70 is influenced by several pathophysiological processes, such as recovery from exercise, the process of repairing damaged tissues, and the reduction of oxidative stress due to inflammation [55].…”
Section: Exercisementioning
confidence: 99%
“… 40 As expected, there is also a negative correlation of eHSP70 with insulin levels and HOMA-IR in overweight young men. 196 Increased eHSP72 levels are associated with sarcopenia 197 and duration of T2DM. 198 On the other hand, conditions that stimulate the tonus of the sympathetic nervous system (as probably occurring during saunas and hot tubs) can augment HSP70 release from immune cells.…”
Section: The Integrity Of the Hsr Can Be Assessed By The Heck Index A...mentioning
confidence: 99%